Respuesta :

Answer:

[tex]x_1 = -2 + 2i\\\\x_2 = -2 -2i[/tex]

Step-by-step explanation:

In this problem we have the equation of the following quadratic equation and we want to solve it using the method of square completion:

[tex]7x ^ 2 + 28x +56 = 0[/tex]

The steps are shown below:

For any equation of the form: [tex]ax ^ 2 + bx + c = 0[/tex]

1. If the coefficient a is different from 1, then take a as a common factor.

In this case [tex]a = 7[/tex]. Then:

[tex]7(x ^ 2 + 4x) = -56[/tex]

2. Take the coefficient b that accompanies the variable x. In this case the coefficient is 4. Then, divide by 2 and the result squared it.

We have:

[tex]\frac{4}{2} = 2\\\\(\frac{4}{2})^2 = 4[/tex]

3. Add the term obtained in the previous step on both sides of equality, remember to multiply by the common factor [tex]a = 7[/tex]:

[tex]7(x ^ 2 + 4x + 4) = -56 + 7(4)[/tex]

4. Factor the resulting expression, and you will get:

[tex]7(x + 2) ^ 2 = -28[/tex]

Now solve the equation:

Note that the term [tex]7(x + 2) ^ 2[/tex] is always [tex]> 0[/tex] therefore it can not be equal to -28.

The equation has no solution in real numbers.

In the same way we can find the complex roots:

[tex]7(x+2)^2 = -28\\\\(x+2)^2 = -\frac{28}{7}\\\\x+2 = \sqrt{-\frac{28}{7}}\\\\x = -2 + \sqrt{-4}\\\\x = -2 + 2\sqrt{-1}\\\\x_1 = -2 + 2i\\\\x_2 = -2 -2i[/tex]

Answer:

x = -2+2i   or  x = -2-2i

Step-by-step explanation:

We have given the equation:

7x² +28x+56 = 0

We have to solve it by completing the square.

7x² +28x+56 = 0

7( x² + 4x + 8) = 0

( x² + 4x + 8)  = 0

x²+2(x)(2) +2² = -8+2²

(x+2)² = -8 +4

(x+2)² = -4

Taking square root on both sides we get,

x+2 = √-4

(x+2) =  ±2i                  as    (√i = -1)

x+2 = 2i   or  x+2 = -2i

x = -2+2i   or  x = -2-2i is the answer.